Multimedia in Cultural Heritage Manuscripts: Integrating Description, Transcription, and Image Content. (16th November 2009) - Calistru Calistru, Catalin Catalin; Ribeiro Ribeiro, Cristina Cristina; David David, Gabriel Gabriel
Abstract : Cultural heritage documents are often subject to digitization processes resulting in image material, even for textual contents. It is therefore common, in collections of valuable documents, to have descriptive information generated by the institutions, along with digitized images, transcriptions created by scholars, translations and even miscellaneous annotations. To offer a faceted access to the collection it is necessary to explore these diverse materials, integrate them according to a model that accounts for both metadata and the content and provide a comprehensive retrieval environment. In this work we have applied the MetaMedia multimedia database framework to a collection of ancient documents, processed the documents in their descriptive, textual, and image content and produced a browsing and searching system. The main challenges are the integrated management of metadata and content, the indexing of the image content, and the design of the browsing and searching interface where various views on the data are kept together.